ショウワキチ デ サイシュシタ ナンキョクサン コウソウ Phyllophora antarctica ノ チョウキ バイヨウ - 大野, 正夫; オオノ, マサオ; 金銅, 義隆; コンドウ, ヨシタカ; 鳥羽山, 照夫; トバヤマ, テルオ; 榊原, 茂; サカキバラ, シゲル; 星合, 孝男; ホシアイ, タカオ; Ohno, Masao; Kondo, Yoshitaka; et al. (1999)
P(論文) 1982年1月(23次)及び1985年1月(26次)に, 昭和基地地先の氷結していた北の瀬戸で, つぶ籠を用いて採集したウニの棘上に付着した南極特産紅藻のPhyllophora antarcticaとPhycodrys antarcticaを採取した。1982年1月に採取したPhyll. antarcticaの葉体は, 日本に持ち帰った後, ガラス製飼育水槽内(幅60cm, 奥行30cm, 高さ45cm, 65L)で, 館内に注入される海水を用い循環式流水で動物との混合で通気培養を行った。水温は-1.9～1.5℃, 光条件は10W白色蛍光灯1本で照射し12時間明期, 12時間暗期にした。葉体は成長につれ叉状分岐していったが, 同時に葉縁から新しい幼葉が生じてこれも成長した。幼葉は成長ととも分岐していった。老いた部位には珪藻やらん藻などの微細藻類が着生し濃紅色になりちぎれやすくなった。葉体は飼育水槽内で16年間生存したが, 10cm以上の大きさにまで成長する葉体は少なかった。葉体には果胞子襄などの生殖器官はみられず栄養成長だけで増加した。1985年1月に採取したPhyll. antarcticaの葉体を腰高シャーレに入れ, 5℃の低温庫内で, 5-50μE/(cm)^<-2>・s^<-1>の光量で12時間明期, 12時間暗期で静置培養を続けた。この場合にも葉縁から幼葉が生じ成長した。しかも, 葉体は水槽通気培養の場合と比較すると小さく2-3cmの葉長にとどまった。葉体を入れた腰高シャーレをアルミホイルで覆った連続暗状態にし0℃と5℃で1年間培養したところ, 50%以上が生存した。しかし, 培養期間を3年間にするとほとんどの葉体が死滅した。 Fronds of the Antarctic seaweeds, Phyllophora antarctica and Phycodrys antarctica fronds, attached to sea urchins (Sterechinus neumayeri) caught with a bait-trap, were collected from ice-covered shore of Kita-no-seto Strait near Syowa Station during the 1982 summer. For about three months, Phyll. antarctica fronds were maintained at approximately 0℃ in the refrigerator of the icebreaker FUJI. After April 1982,they were maintained in a glass culture tank at Kamogawa Sea World, Chiba, Japan. Aerated seawater was supplied through a closed re-circulation system; water temperature was kept between -1.9 and 1.5℃ The tank was illuminated with a 10W day-light fluorescent tube (12h light, 12h dark). Phyll. antarctica survived in the tank for 16 years. Producing new growth at the margin of the original fronds, the old parts decayed. Consequently the biomass of fronds increased 20-30 times. It was noted that the biomass increase was greater with the cohabitation of such animals as fish, echinoids, asteroids, gastropods and nemertineans than that when the seaweeds were maintained without animals. In the 1985 summer, fronds of the same Phyll. antarctica were again collected by the same method. The fronds were taken to the Usa Marine Biological Institute, Kochi University, Japan. Those ...